2015
DOI: 10.3748/wjg.v21.i26.8125
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for complications associated with upper gastrointestinal foreign bodies

Abstract: In cases of longer than 12 h since foreign body ingestion or sharp-pointed objects, rapid endoscopic intervention should be provided in patients with ingested foreign bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
132
4
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(143 citation statements)
references
References 25 publications
3
132
4
4
Order By: Relevance
“…3 Recent Korean study also showed fish bone as the most common foreign body. 4 There was no significant difference in the type of foreign body between cases and controls. In other words, foreign body type was not found to have a role in predicting the complications.…”
Section: But In Previous Studymentioning
confidence: 78%
See 1 more Smart Citation
“…3 Recent Korean study also showed fish bone as the most common foreign body. 4 There was no significant difference in the type of foreign body between cases and controls. In other words, foreign body type was not found to have a role in predicting the complications.…”
Section: But In Previous Studymentioning
confidence: 78%
“…In oesophagus, upper oesophagus was the most common site of impaction found in the recent Korean study. 4 There was statistically significant association between the site of FB impaction and complications.…”
Section: But In Previous Studymentioning
confidence: 87%
“…While most ingested foreign bodies (80%-90%) are passed spontaneously, the remaining 10%-20% require endoscopic removal, and in less than 1% of the cases impactions, perforations, and obstructions require surgical interventions [2]. Inflammation, abscess formation, peritonitis, obstruction, fistulas, and bleeding may develop leading to mortality and morbidity [5]. In addition, migration of the foreign bodies to the neighboring organs can be observed infrequently [1].…”
Section: Discussionmentioning
confidence: 99%
“…The balloon was inflated distal to the fish bone, which released the bone on one side, this being accompanied by a discharge of pus. A grasping forceps (FG-44NR-1; Olympus, Zoeterwoude, The Netherlands) was inserted via the second channel to retrieve the bone, removing it whole without additional injury [1,2]. Because the mucosa was only mildly damaged, it was not necessary to perform an esophagogram.…”
mentioning
confidence: 99%